'Questions concerning attention and Stiegler's therapeutics'. Issue 4 (20th March 2020) - Fitzpatrick, Noel
Abstract: The article sets out to develop the concept of attention as a key aspect to building the possible therapeutics that Bernard Stiegler's recent works have pointed to ( The Automatic Society, 2016, The Neganthropocene, 2018 and Qu'appelle-t-on Panser, 2018). The therapeutic aspect of pharmacology takes place through processes that are neganthropic; therefore, which attempt to counteract the entropic nature of digital technologies where there is flattening out to the measurable and the calculable of Big Data. The most obvious examples of this flattening out can be seen in relation to the use of natural language processing technologies for text interpretation and the use of text analytics alongside student analytics. However, the process of exosomatisation of knowledge takes place in forms of hypomnesic tertiary retentions or digital technologies. The loss of knowledge is inherent to these processes of exteriorisation, this loss of knowledge takes place through a process proletarianisation which Marx had pointed to in the Grundisse (1939). The therapeutic gesture is, therefore, an intrinsically educational one, where the loss of knowledge of the pharmacological nature of digital technologies is counteracted by other forms of knowledge construction that can be enabled by digital technologies. Hence, there is a profound educational gesture necessary to enable the re-harnessing of technology to enable the therapeutics. This paper will argue that the positive re-harnessing, the therapeutics, can take place through the development of new forms of neganthropic gestures which can be afforded by the development of specific forms of digital technologies. These also enable a contributive research process whereby the rationalisation of the production of knowledge within the university can be challenged by collaborative, interpretative processes of knowledge production.